Marketing Strategies Implemented by the Sales Force in Promoting the Berkah Pension Financing Product at BSI KCP Kediri Gudang Garam - Ajeng Custhya Wardani; Tiara Widya Antikasari; Na'ima Muhimmatul Fitria (Falahiya Journal of Islamic Banking and Finance, 2025)
Introduction: BSI KCP Kediri Gudang Garam faces challenges in introducing Pembiayaan Pensiun Berkah amid the dominance of conventional banks. This financing product targets retirees and prospective retirees, including civil servants, members of the Indonesian National Armed Forces, the Indonesian National Police, and widows of retirees, to meet post-retirement financial needs in accordance with Sharia principles. Research Methods: A descriptive qualitative approach was employed, using observation, interviews, and documentation as data collection techniques. Results: Customer education and personalized services are effective in increasing customer understanding and strengthening the bank’s Sharia-compliant image. However, the overall effectiveness of the strategy remains limited due to constraints in human resources and market coverage. Conclusion: Although the strategy contributes to customer loyalty, it has not significantly increased the number of customers. Strengthening sales force capacity and adopting a local-needs-based approach are therefore essential to optimize marketing performance.